Determination of Total Flavonoid, Iron (Fe) and Chlorophyll Content of Brazilian Spinach Extract (Althernanthera sisso) based on Different Types of Extraction Solvents - Ratih, Gusti Ayu Made; Heri Setyo Bekti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Brazilian spinach (Alternanthera sissoo) is known to contain various bioactive compounds such as flavonoids, iron (Fe), and chlorophyll that have the potential to be utilized in the health and food fields. However, the levels of these compounds can vary depending on the type of solvent used in the extraction process, so research is needed to determine the most effective solvent. Brazilian spinach (Alternanthera sissoo) is a vegetable species originally from Brazil that has begun to be cultivated in Indonesia. It contains secondary metabolites such as flavonoids, alkaloids, steroids, and saponins. Additionally, this plant has relatively high levels of iron and chlorophyll compared to other vegetables, with chlorophyll playing an important role in treating anemia and assisting the body in utilizing iron. This study aims to analyze the most effective solvent for extracting total flavonoids, iron (Fe), and chlorophyll from Brazilian spinach, supporting its potential development as a food supplement ingredient. This research employed a quasi-experimental design using a completely randomized design (CRD). The samples were Brazilian spinach extracted with 70% ethanol, ethyl acetate, and methanol. The concentrations of the compounds were determined using UV-Vis spectrophotometry and Atomic Absorption Spectrophotometry (AAS). The results showed that methanol extraction produced the highest extract yield (10.87%), the highest iron content (10.205 mg/kg), chlorophyll content of 13,586.571 mg/kg, and total flavonoids of 900.128 mg/100gQE. Based on these findings, methanol was identified as the most effective solvent for extracting bioactive compounds from Brazilian spinach. These results imply that Brazilian spinach has strong potential to be developed as a natural source for food supplements.